2005
DOI: 10.1007/s10926-005-8032-1
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-Based Return-to-Work Interventions: Optimizing the Role of Stakeholders in Implementation and Research

Abstract: Recommendations for future research include developing methods for engaging stakeholders, determining the optimal level and timing of stakeholder involvement, expanding RTW research to more diverse work settings, and developing RTW interventions reflecting all stakeholders' interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
191
0
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(206 citation statements)
references
References 63 publications
5
191
0
10
Order By: Relevance
“…A multi-stakeholder or a system approach to return-to-work is supported by an increasing number of studies [1][2][3]. Cooperation, though identified as a cornerstone of successful return-to-work, is challenging due to incompabilities between stakeholders regarding policies and definitions of concepts [1].…”
Section: Introductionmentioning
confidence: 99%
“…A multi-stakeholder or a system approach to return-to-work is supported by an increasing number of studies [1][2][3]. Cooperation, though identified as a cornerstone of successful return-to-work, is challenging due to incompabilities between stakeholders regarding policies and definitions of concepts [1].…”
Section: Introductionmentioning
confidence: 99%
“…It was evident that they needed practical and personal support from their seniors to effectively discharge this challenging responsibility [12,53]. Two closely related aspects of the context were the impact of differing -41 -perceptions and beliefs and of the quality of human relationships amongst stakeholders.…”
Section: Contextual Factors With More Widespread Effectsmentioning
confidence: 99%
“…Recent reviews have noted the low methodological quality of much of the research [1,11,12]; and uncertainty is compounded by the impact of the cultural, political and organisational contexts in which SA occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several stakeholders involved in RTW processes (most commonly workers, employers, insurance representatives and healthcare professionals), all representing different perspectives [8]. In relation to CMDs, it has been suggested that supervisors and physicians focus on at-work functioning and sustainability, while workers tend to include more aspects such as work-home-balance, mental functioning and job satisfaction [9].…”
Section: Introductionmentioning
confidence: 99%